Theory of smoothness of movement of multiple-axle agricultural combined tractor-implement units - Bulgakov, V.; Kuvachov, Volodymyr; Кувачов, Володимир Петрович; Кувачев, Владимир Петрович; Olt, J. (My University, 2020)
The smoothness of movement of modular power units operated as parts of agricultural combined units, which are multiple-axle process systems, is a most important performance criterion. The research into the elastic damping properties of the process module of the modular power unit is of certain interest, because it could provide for a substantial reduction of the dynamic load on the transmission and engine of the power unit (module). The aim of the research is to improve the smoothness of movement of the modular power unit as part of an agricultural combined unit by means of developing an elastic damping link between the power module and the process module. The research resulted in finding new patterns of the impact that the parameters of the elastic and dissipative link between the two modules had on the characteristics of the vertical oscillations of the modular power unit. It was proved that by applying the rational rigidity of the elastic and dissipative link between the two modules it was possible to achieve the desired amplitude-frequency and correlationspectrum characteristics and reduce the dispersions of the oscillations of the modular power unit by a factor of 3-4. The rational rigidity of the elastic and dissipative link between the two modules in the ploughing process was observed at a resistance coefficient value of 1.65 kN·s·m–1.
Keywords: modular power unit; optimal design; product modelling; smoothness of movement; vertical oscillation